Does leptin associate with testosterone and exercise-induced muscle damage among professional athletes? - Zhang, X.; Shao, J.; Bai, Y.; Jin, A.; An, N.; Xiang, M.; Fang, Z.; Wang, Q.; Li, J.; Yi, M.; Han, Q. (Medicina dello Sport, 2024)
BACKGROUND: The purpose of this study was to investigate the association between leptin and sex hormone and its correlation with exercise-induced muscle damage (EIMD).